Developing Innolysins Against Campylobacter jejuni Using a Novel Prophage Receptor-Binding Protein - Zampara, Athina; Sørensen, Martine C. Holst; Gencay, Yilmaz Emre; Grimon, Dennis; Kristiansen, Sebastian Hougaard; Jørgensen, Lallana Skaarup; Kristensen, Josephine Rejgaard; Briers, Yves; Elsser-Gravesen, Anne; Brøndsted, Lone (Frontiers in Microbiology, 2021)
Campylobacter contaminated poultry remains the major cause of foodborne gastroenteritis worldwide, calling for novel antibacterials. We previously developed the concept of Innolysin composed of an endolysin fused to a phage receptor binding protein (RBP) and provided the proof-of-concept that Innolysins exert bactericidal activity against Escherichia coli. Here, we have expanded the Innolysin concept to target Campylobacter jejuni. As no C. jejuni phage RBP had been identified so far, we first showed that the H-fiber originating from a CJIE1-like prophage of C. jejuni CAMSA2147 functions as a novel RBP. By fusing this H-fiber to phage T5 endolysin, we constructed Innolysins targeting C. jejuni (Innolysins Cj). Innolysin Cj1 exerts antibacterial activity against diverse C. jejuni strains after in vitro exposure for 45 min at 20 °C, reaching up to 1.30 ± 0.21 log reduction in CAMSA2147 cell counts. Screening of a library of Innolysins Cj composed of distinct endolysins for growth inhibition, allowed us to select Innolysin Cj5 as an additional promising antibacterial candidate. Application of either Innolysin Cj1 or Innolysin Cj5 on chicken skin contaminated with C. jejuni CAMSA2147 led to 1.63 ± 0.46 and 1.18 ± 0.10 log reduction of cells, respectively, confirming that Innolysins Cj can kill C. jejuni in situ. Identification of other unexplored Campylobacter phage RBPs may further increase the repertoire of new Innolysins Cj targeting distinct receptors and working as antibacterials against Campylobacter.